Radikalisme Atas Nama Agama dalam Perspektif Intelektual Muda di Tengah Realitas Multikultural - Gina Lestari (Khazanah Theologia, 2021)
The reality of Indonesian multiculturalism is the fortune and wealth as far as its diversity is recognized, internalized, and responded with tolerance. If plurality becomes the separator that forms the symbol of a group and personal ego, then plurality becomes the cause of dispute, intolerance, and even radicalism. The cases of violence in the name of religion target all levels of society, including young intellectuals. This study aims to observe the scholar's perspective on radicalism in the name of religion in multicultural reality. The samples were 649 fourth semesters scholars in ITB, UNPAD, UPI, UIN Sunan Gunung Jati, UNPAS, UNISBA, and POLBAN in 2012. According to the research, most of the students have a good multicultural understanding. 65% of respondents have an awareness of accepting and appreciating differences, and 63% accept and appreciate differences in religious activities. Only 2% (almost always) and 32% (sometimes) commit acts of discrimination. However, half of the respondents (42% slightly agree and 8% agree) have an intolerant view. 21% of respondents slightly agree, and 3% agreed to view jihad as synonymous with violence. Surprisingly, 22% of respondents slightly agree, and 3% agreed to interpret jihad as terrorism. Moreover, 15% of respondents slightly agree, and 2% agreed to view suicide bombing as an act of jihad. Young intellectuals should have a clear understanding of jihad both etymologically or epistemologically. Overcoming the phenomenon of radicalism must depart from the core of the problems. One method is de-radicalization to straighten out a narrow-minded in a friendly, tolerant, peaceful, and humane way in the social, political, economic, and educational fields.